Structural growth of zinc oxide nanograins on carbon cloth as flexible electrochemical platform for hydroxychloroquine detection. (January 2023) - Kokulnathan, Thangavelu; Wang, Tzyy-Jiann; Murugesan, Thangapandian; Anthuvan, Allen Joseph; Kumar, Rishi Ranjan; Ahmed, Faheem; Arshi, Nishat
Abstract: Pharmaceutical pollution that imposes a health threat worldwide is making accurate and rapid detection crucial to prevent adverse effects. Herein, binder-free zinc oxide nanograins on carbon cloth (ZnO NGs@CC) have been synthesized hydrothermally and employed to fabricate a flexible electrochemical sensor for the quantification of hydroxychloroquine (HCQ) that is typical pharmaceutical pollution. The characteristics of ZnO NGs@CC were investigated by various in-depth electron microscopic, spectroscopic and electroanalytical approaches. Compared with the pristine CC platform, the ZnO NGs@CC platform exhibits superior electrochemical performance in detecting HCQ with a large oxidation current at a low over-potential of +0.92 V with respect to the Ag/AgCl (Sat. KCl) reference electrode. With the support of desirable characteristics, the fabricated ZnO NGs@CC-based electrochemical sensor for HCQ detection displays good performances in terms of wide sensing range (0.5–116 μM), low detection limit (0.09 μM), high sensitivity (0.279 μA μM −1  cm −2 ), and strong selectivity. By the resulting 3D hierarchical nanoarchitecture, ZnO NGs@CC has progressive structural advantages that led to its excellent electrochemical performance in sensing applications. Furthermore, the electrochemical sensor is employed to detect HCQ in biological and environmental samples and also achieves good recovery rates. Thus, the designed ZnO NGs@CC demonstrates admirable electrochemical activity toward HCQ real-time monitoring and would be an excellent electrochemical platform for HCQ sensing. Graphical abstract: Image 1 Highlights: The ZnO NGs@CC is synthesized by hydrothermal method. The ZnO NGs@CC based electrochemical sensor possesses excellent electrocatalytic activity for HCQ. The fabricated ZnO NGs@CC sensor exhibited excellent analytical performance. The practicability of fabricated ZnO NGs@CC sensor was validated by spiking and recovery technique.